NURSE ACTION DURING TRAINING SUPERVISED IN A UNIVERSITY HOSPITAL IN NATAL-RN: TENDENCY AND EDUCATIONAL PREPARATION (Fiep Bulletin - online, 2014)
Introduction: Nursing is one of professions of health area that the essence and specificity is the care of the human being, individually, at family or in the community. Currently, the nursing professionals have tried hard to the care practice in a holistic view, aiming the appreciation of the man and be total both in the field of health as when performing functions of teaching, research and extension, considering changes in the educational system. Driven by the issues of education in nursing, focalizing on the agent educator, we have as goal identify if the nurses fell that they are educationally prepared to act as training supervise and which are the educational tendencies that they classified their educational practice. Methodology: study which was to focus on the central pedagogical practice of nurse during training supervised at Hospital Universitário Onofre Lopes (HUOL) in Natal, conducted with a sample that intentional of 22 nurses working as supervisors with the training of graduate students and average level of nursing, who answered a questionnaire structured. Results: We checked that predominance women(90,1%) , 63,6% had specializations in different areas, 59,1% had PROFAE specialization, 45,4% had undergraduate course in nursing and just 4,5% have master course. 81,8% of the surveyed felt prepared to act as training supervise placing their educative practice in the constructivist Tendency(45,4%), Critical-Reflexive(13,7%) and Traditional(13,7%). Talking about on the local educational activities were predominant the wards (72.7%) and ICU (13.6%), with emphasis on the actions of report / notes (100.0%) of nursing notes (95.5%) , individual guidance (90.9%), transition from nasogastric tube and bladder gall (90.9%), vein puncture (90.9%) and make curative (86.4%). Conclusion: The surveyed mostly had an incoherence between their pedagogic practice done and the educational Tendency that they placed their actions in the process of teaching, showing an unknowing of the conceptual aspects and characteristics of the pedagogic approaching.
Keywords: Pedagogic Practice; Education in Health; Nurse